If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + -8 + 3x = 24 Reorder the terms: -8 + -11x + 3x = 24 Combine like terms: -11x + 3x = -8x -8 + -8x = 24 Solving -8 + -8x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -8x = 24 + 8 Combine like terms: -8 + 8 = 0 0 + -8x = 24 + 8 -8x = 24 + 8 Combine like terms: 24 + 8 = 32 -8x = 32 Divide each side by '-8'. x = -4 Simplifying x = -4
| 2(-7x+6)=-16-7x | | 5.9x=-30.09 | | -5=7+4x | | 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 |